A Tool for Product Derivation and Semi-Automatic Deployment of Web-Based Systems - Canuto, Jackson Meire Dantas; Kulesza, Uirá; Lopes, Frederico (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
This paper presents a tool for product derivation and semi-automatic deployment of web-based systems. The tool focuses on cloned web-based systems implemented using the PHP language, which are refactored to become software product lines. The paper also reports the results of a case study of using the tool in the context of a large scale web-based system. Our findings show some preliminary evidence of the benefits of the tool to reduce: (i) the time of product derivation and deployment; and (ii) the manual effort to customize existing cloned web-based systems.